Analyzing the Influence of Taxpayer Awareness and Sanctions on Compliance in Motor Vehicle Tax Payments: Evidence from Jayapura City - Kambu, Hendrik; Urip S, Transna Putra; Titalessy, Pisi Bethania; Somisu, Rut Penina; Harikedua, Alfani Laura; Rumalutur, Tince (AIBPM Publisher, 2025)
Motor vehicle tax is a vital source of Local Own-Source Revenue in Jayapura City, yet low taxpayer compliance continues to hinder optimal revenue collection. This study examines how taxpayer awareness and tax penalties influence compliance with motor vehicle tax payments. Using a quantitative approach, data were collected through questionnaires and analyzed with multiple linear regression to assess both partial and simultaneous effects of the independent variables. The results reveal that taxpayer awareness does not have a significant impact on compliance, as shown by a significance value of 0.886, which is higher than the 0.05 threshold. Conversely, tax penalties demonstrate a positive and statistically significant effect, with a significance value below 0.001. Furthermore, simultaneous testing indicates that both variables significantly affect compliance, with an F value of 31.470 and an R² value of 0.473, meaning that 47.3% of the variation in compliance is explained by the model. These findings suggest that strict and consistent enforcement of tax penalties is more effective in improving taxpayer compliance than relying solely on awareness efforts, offering valuable insights for local governments to enhance motor vehicle tax revenue.